The Implementation of Green Adventure Learning to Enhance Gross Motor Skills in Children Aged 5–6 Years - Khusnul Khatimah; Sukrin; Hermansyah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aims to examine the implementation of Green Adventure Learning in supporting the development of gross motor skills in early childhood. The research employed a descriptive qualitative approach conducted at Qonita Preschool, involving Group B children as the research participants. Data were collected through classroom observations, documentation, and field notes to obtain a detailed description of learning activities and children's motor skill engagement during the program. Data analysis was carried out using the stages of data reduction, data display, and conclusion drawing. To ensure the trustworthiness of the findings, the study applied source triangulation, prolonged observation, and careful documentation of learning activities. The findings indicate that the implementation of Green Adventure Learning involved outdoor exploration, movement-based games, and direct interaction with natural environments. These activities provided opportunities for children to practice balance, coordination of movement, agility, and muscle use during learning sessions. Observations during the learning process showed that children participated actively in physical activities and demonstrated greater involvement in movement tasks provided by the teacher. The learning environment also reflected contextual and child-centered practices, where children were encouraged to explore and engage physically with their surroundings. Overall, the implementation of nature-based learning activities through Green Adventure Learning offers meaningful experiences that can support gross motor skill development in early childhood education settings.